2014
DOI: 10.1177/2325957414555227
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in ART-Naive HIV-Infected Persons in Nigeria—Implications for Care

Abstract: A significant burden of dyslipidemia exists among ART-naive HIV-infected persons. Low HDL-C was the most frequently observed abnormality. The abnormalities related more with viral load levels than with CD4 counts. Dyslipidemia screening should be done in ART-naive HIV-infected persons. Simple healthy lifestyle changes should be emphasized, with other care given to those with the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
8
11
1
Order By: Relevance
“…Those who had higher level of HIV RNA had a higher atherogenic risk profile. This is consistent with the previously reported studies which showed HDL-C was negatively correlated with viral load and the TG levels was positively correlated with viral load on the contrary [11, 22, 26]. These studies also demonstrated AIP or lipids parameters correlated with immunologic status of HIV infected people.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Those who had higher level of HIV RNA had a higher atherogenic risk profile. This is consistent with the previously reported studies which showed HDL-C was negatively correlated with viral load and the TG levels was positively correlated with viral load on the contrary [11, 22, 26]. These studies also demonstrated AIP or lipids parameters correlated with immunologic status of HIV infected people.…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for the TG difference may be the differed degrees of immunosuppression of the HIV infection patients. A study conducted in Nigeria showed that the TG levels were reversely correlated with CD4 counts and positively correlated with viral load [11]. The HIV infected participants in our study had a better immune status as reflected by a median CD4 cell count of 404.0 (281.5–531.5) cell/μl in the AHI group and 173.0 (104.3–243.2) in the CHI group compared to previous studies.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations